Effect of test atmosphere composition on high-temperature oxidation behaviour of CoNiCrAlY coatings produced from conventional and ODS powders. (4th May 2018) - Huang, T.; Bergholz, J.; Mauer, G.; Vassen, R.; Naumenko, D.; Quadakkers, W. J.
Abstract: The oxidation behaviour of free-standing CoNiCrAlY coatings produced by low-pressure plasma spraying using conventional powder and oxide dispersion strengthened (ODS) powder containing 2 wt. % Al-oxide dispersion was investigated. Thermogravimetric experiments at 1100 °C in Ar-20%O2 and Ar-4%H2 -2%H2 O showed lower oxidation rates of the ODS than the conventional coating. In the latter material the scale growth was enhanced by extensive Y-incorporation of Y/Al-mixed oxide precipitates in the scale and apparently by Y-segregation to oxide grain boundaries. In the ODS coating the alumina dispersion bonded Y in the form of Y-aluminate thereby effectively suppressing scale 'overdoping'. SEM/EBSD studies of all alumina scales revealed a columnar grain structure with the lateral grain size increasing approximately linearly with depth from the oxide/gas interface. For both coatings the alumina scale growth was slower in Ar–H2 –H2 O than in Ar–O2 . The result is believed to be related to a lower oxygen potential gradient and to slower grain boundary diffusion in the scale forming in H2 /H2 O containing gas.